Fears, violence and student condition in contexts of urban marginality - Hernán Arévalos, Dario (2020)
The present article sets out to analyze from a socio-educational perspective the relationships between the emotional experiences and the student condition of young people from popular sectors. The testimonies collected from students from two secondary schools located in peripheral urban areas allow us to examine how the conditions of vulnerability marked by the degradation of the social fabric, mistrust and uncertainty structure affective life. The existential fears are revealed due to the arbitrariness of the police apparatus and the dangerous situations involved in traveling through the neighborhood where they live. It is concluded that the school occupies a central place as a space of pacification of the bonds valued and recognized by the interviewees.